The Hope of Indonesian Students: Current and Future Counseling Challenges - Ipah Saripah; Nur Asiah (Bisma The Journal of Counseling, 2023)
Hope is a component of the character strength dimension, combining goal-achieving plans (pathways thinking) and goal-achieving encouragement (agency thinking). Hope correlates with various factors in individuals' development and lives (personal, social, academic, and career), but few aspects related to the pandemic have yet to be revealed, particularly in Indonesia. Therefore, to bridge the gap, this study aims to uncover the hope of the 324 senior high school students who voluntarily participated in this research and came from several provinces and regions in Indonesia. The study used descriptive quantitative methods based on the Hope Scale. The data was provided using a Google form and analyzed using Excel and the JASP 0.16.1.0 software. The results showed that 58.3% of students were in the deficient category. There is a difference in the proportion of hope between males and females based on gender. Furthermore, the Sundanese ethnicity has the lowest hopes of all the ethnic groups. The findings may assist certain parties, such as school counselors, in identifying alternative solutions to help students and emphasizing and paying attention to adolescents for them to develop hope.